Hazardous Effects of Malaria for Patients Residing in Low-probability Malaria Areas: A Case Report and Critiques of the Literature for Cerebral Malaria - Nzayikorera, Janvier (Journal of Community Medicine and Health Solutions, 2023)
Despite decades of global and country commitments towards eradicating malaria, malaria remains the most hazardous parasitic disease and the most common cause of fever for humans, especially in tropical countries. Plasmodium falciparum causes 90% of malaria cases. Coma [Cerebral Malaria (CM)], acidosis, hypoglycemia, severe anemia, renal dysfunction, and pulmonary edema are the most common complications of malaria caused by Plasmodium falciparum and the most common cause of death related to malaria. People from less prevalent malaria areas are at high risk of developing these complications. A 16-year-old male from a low malaria transmission area was diagnosed with CM. Prior to developing CM, he was treated with Coartem. CM is a medical emergency and one of the forms of severe malaria. CM has high mortality and morbidity rates. Yet, international health-related agencies, funders, and policy-makers are unfamiliar with it. The continuous occurrence of CM validates the considerable need for global investment in malaria control and elimination programs. Early administration of Artesunate to all patients suspected of having severe malaria would reduce global malaria-related mortality and morbidity. Simple tests, such as the determination of malaria parasitic density either with thin or thick blood smears, may influence the proper management of all severe malaria cases. However, in clinical practice, the determination of malaria parasitic density is not routinely done. Further commitments are needed to ensure routine determination of malaria parasitic density for all suspected severe malaria cases. Moreover, further commitments are needed to guarantee the proper management of CM because it is a major cause of reversible encephalopathy in tropical countries.